EFFECT OF PHOSPHORUS AND SULPHUR ON GROWTH AND YIELD OF GROUNDNUT (Arachis hypogaea L.) - NARREDDY HINDUJA; SHIKHA SINGH; DHANANJAY TIWARI; BHISHEK MAHAPATRA; B . SHEKHAR MAHANTA (The Bioscan, 2020)
A field experiment was conducted in the crop research farm of SHUATS, Prayagraj to know the effect of phosphorus and Sulphur on growth and yield of groundnut. The experiment consisted of 10 treatments which includes three levels of phosphorus (40, 55 and 70 kg/ha) and Sulphur (20, 30 and 40 kg/ha). The treatment receiving 70 kg phosphorus + 40 kg Sulphur/ha produced significantly higher plant height (60.36 cm), Kernel (2.37 t/ha), pod yield (3.26 t/ha), total number of pods/plant (20) and 100 kernel weight (43.33 g). However, Net returns (138787.30 rs/ha) and B: C ratio (1.82) was also obtained maximum with the application of 70 kg phosphorus + 40 kg Sulphur/ha. This experiment shown treatment receiving 70 kg phosphorus+ 40 kg Sulphur/ ha was more productive as well as economic also.